2014
DOI: 10.3945/ajcn.114.089706
|View full text |Cite
|
Sign up to set email alerts
|

Association between Mediterranean and Nordic diet scores and changes in weight and waist circumference: influence of FTO and TCF7L2 loci

Abstract: A high MDS is associated with a lower ΔWC and ΔWCBMI, regardless of FTO and TCF7L2 risk alleles. For Δweight, findings were less clear, but the effect may depend on the TCF7L2 rs7903146 variant. The NDS was not associated with anthropometric changes during follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 46 publications
5
41
0
2
Order By: Relevance
“…22 This finding was further supported by a study in 1,381 first-time coronary heart disease patients and 4,290 population controls, which showed that there was no interaction between the FTO rs9939609 variant and macronutrient intake on body mass index. 28 To overcome the challenges involved in examining single genes, several studies have examined the combined effect of genes/gene variants on metabolic outcomes in response to dietary intake.…”
Section: Measuring Gene-nutrient Interactionssupporting
confidence: 53%
See 2 more Smart Citations
“…22 This finding was further supported by a study in 1,381 first-time coronary heart disease patients and 4,290 population controls, which showed that there was no interaction between the FTO rs9939609 variant and macronutrient intake on body mass index. 28 To overcome the challenges involved in examining single genes, several studies have examined the combined effect of genes/gene variants on metabolic outcomes in response to dietary intake.…”
Section: Measuring Gene-nutrient Interactionssupporting
confidence: 53%
“…[12][13][14] Although many genetic variants have been identified for obesity and type 2 diabetes using candidate gene 15 and genome-wide association studies, 16,17 it has been shown that these variants do not cause metabolic diseases without an obesogenic dietary exposure. 18 Several candidate gene studies have examined gene-diet interactions [19][20][21][22] ; however, most of the studies were small and hence the findings have been inconsistent.…”
Section: Measuring Gene-nutrient Interactionsmentioning
confidence: 98%
See 1 more Smart Citation
“…As far as we know, our study is the first to show a prospective interaction between the TCF7L2-rs7903146 polymorphism and T2D in determining BMI (up to six years). This is also important as other studies have focused on gene–diet interactions on weight changes involving the TCF7L2 polymorphism [48]. In these studies stratification by T2D status should be considered to reduce the confounding effect of this heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…The waist circumference was measured by using non-elastic tape with an accuracy of 0.5 cm in the middle of the distance between last rib and iliac crest bone [19]. BMI was calculated as weight in kilograms divided by the square of height in meters.…”
Section: Subjectsmentioning
confidence: 99%